(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study explores the impact of community service learning programs on student leadership development, social skills, and academic performance. Using a qualitative research approach, including case studies, surveys, and interviews, the study highlights the significance of experiential learning in fostering civic responsibility and career readiness. Findings indicate that student participation in community service enhances confidence, leadership abilities, social awareness, and emotional intelligence. The study emphasizes the need for structured service-learning programs within educational institutions to support student engagement and long-term personal and professional growth. Policy recommendations suggest integrating service-learning into curricula and establishing university-community partnerships to maximize its impact.